DIAGNOSTIC CONSIDERATION OF RADIAL IMAGING METHODS IN IDENTIFYING LOCAL RECURRENCE OF PROSTATE CANCER AFTER RADICAL PROSTATECTOMY - E. A. Bezrukov; E. L. Lachinov; G. A. Martirosyan (Вестник урологии)
The diagnostic consideration of the most commonly used methods of radial diagnostics in identifying local recurrence of prostate cancer after radical prostatectomy in patients with biochemical recurrence is reflected in the literature review. The identified level of PSA after radical prostatectomy can argue for both local recurrence, the presence of tumor dissemination, and a residual prostate tissue without tumor that was left on the edge of the cut. With the purpose of early diagnosis of prostate cancer recurrence, it is advisable to monitor PSA levels after 3 months after radical prostatectomy. In case of growth of PSA levels after radical prostatectomy, it is necessary to answer the question: whether the recurrence is local or metastatic. Modern imaging methods, such as transrectal ultrasound examination, bone scanning, multislice computed tomography, positron emission tomography and endorectal magnetic resonance imaging provide excluding or establishing the presence of recurrence of prostate cancer after radical prostatectomy. It should be noted that none of the methods of radiodiagnostics are not ahead of the results of PSA in the identification of local recurrence of prostate cancer after radical prostatectomy; however, in their complex application, prostate cancer recurrent after radical prostatectomy can be visualized at its earliest stages.